A strategy for the next decade to address data deficiency in neglected biodiversity. Issue 2 (2nd September 2020) - Hochkirch, Axel; Samways, Michael J.; Gerlach, Justin; Böhm, Monika; Williams, Paul; Cardoso, Pedro; Cumberlidge, Neil; Stephenson, P. J.; Seddon, Mary B.; Clausnitzer, Viola; Borges, Paulo A. V.; Mueller, Gregory M.; et al.
Abstract: Measuring progress toward international biodiversity targets requires robust information on the conservation status of species, which the International Union for Conservation of Nature (IUCN) Red List of Threatened Species provides. However, data and capacity are lacking for most hyperdiverse groups, such as invertebrates, plants, and fungi, particularly in megadiverse or high‐endemism regions. Conservation policies and biodiversity strategies aimed at halting biodiversity loss by 2020 need to be adapted to tackle these information shortfalls after 2020. We devised an 8‐point strategy to close existing data gaps by reviving explorative field research on the distribution, abundance, and ecology of species; linking taxonomic research more closely with conservation; improving global biodiversity databases by making the submission of spatially explicit data mandatory for scientific publications; developing a global spatial database on threats to biodiversity to facilitate IUCN Red List assessments; automating preassessments by integrating distribution data and spatial threat data; building capacity in taxonomy, ecology, and biodiversity monitoring in countries with high species richness or endemism; creating species monitoring programs for lesser‐known taxa; and developing sufficient funding mechanisms to reduce reliance on voluntary efforts. Implementing these strategies in the post‐2020 biodiversity framework will help to overcome the lack of capacity and data regarding the conservation status of biodiversity. This will require a collaborative effort among scientists, policy makers, and conservation practitioners. Abstract : Article Impact Statement : Global conservation policies require a strategy to obtain robust data for measuring progress against biodiversity targets. Abstract : Una Estrategia para la Siguiente Década para Enfrentar la Deficiencia de Datos de la Biodiversidad Ignorada Resumen: La medida del avance hacia los objetivos internacionales para la biodiversidad requiere información sólida sobre el estado de conservación de las especies, la cual proporciona la Lista Roja de Especies Amenazadas de la Unión Internacional para la Conservación de la Naturaleza (UICN). Sin embargo, los grupos más hiperdiversos, como los invertebrados, las plantas y los hongos, carecen de datos y capacidad, particularmente en regiones megadiversas o de endemismo alto. Las políticas de conservación y las estrategias de biodiversidad dirigidas hacia el cese de la pérdida de biodiversidad para el 2020 necesitan ser adaptadas para solucionar estas insuficiencias de información para después del año 2020. Diseñamos una estrategia de ocho puntos para cerrar las brechas existentes en los datos mediante la reactivación de la investigación exploratoria en el campo sobre la distribución, abundancia y ecología de las especies; la vinculación más cercana entre la investigación taxonómica y la conservación; la mejora a las bases de datos mundiales sobre biodiversidad mediante la presentación obligatoria de datos espacialmente explícitos para las publicaciones científicas; el desarrollo de una base mundial de datos espaciales sobre las amenazas para la biodiversidad para facilitar las valoraciones de la Lista Roja de la UICN; la automatización de las preevaluaciones mediante la integración de datos de distribución y datos de amenazas espaciales; el desarrollo de la capacidad en la taxonomía, la ecología y el monitoreo de la biodiversidad en países con una gran riqueza de especies o endemismos; la creación de programas de monitoreo de especies para los taxones menos conocidos; el desarrollo de suficientes mecanismos de financiamiento para reducir la dependencia de los esfuerzos voluntarios. La implementación de estas estrategias en el marco de trabajo para la biodiversidad posterior al 2020 ayudará a superar la falta de capacidad y datos con respecto al estado de conservación de la biodiversidad. Lo anterior requerirá de un esfuerzo colaborativo entre científicos, formuladores de políticas y practicantes de la conservación. 摘要: 衡量全球生物多样性目标的进展需要关于物种保护状况的可靠信息, 这些信息一般由《世界自然保护联盟 (IUCN) 濒危物种红色名录》提供。然而, 对于大多数多样性高的类群, 如无脊椎动物、植物和真菌, 已有数据和相应能力都十分缺乏, 特别是在多样性或特有性很高的地区。因此, 旨在到 2020 年制止生物多样性丧失的保护政策和生物多样性战略需要做出相应调整, 以便在 2020 年后解决这些信息不足的问题。我们设计了八条战略来填补现有的数据空缺, 分别是: 重新加强对物种分布、丰度和生态的探索性野外研究; 将分类学研究与保护更紧密地结合; 强制要求在发表科学出版物时提交空间显式数据以提升全球生物多样性数据库; 建立生物多样性面临威胁的全球空间数据库以帮助《IUCN 红色名录》的评估; 通过整合分布数据和空间威胁数据来实现自动预评估; 在物种丰富度高或特有性高的国家增强分类学、生态学和生物多样性监测的能力建设; 为所知甚少的类群建立物种监测计划; 建立充分的筹资机制以减少对志愿工作的依赖。我们认为, 在 2020 年后生物多样性框架中实施这些战略, 将有助于克服生物多样性保护状况方面能力和数据匮乏的问题。这将需要科学家、政策制定者和保护实践者之间建立合作。翻译: 胡怡思; 审校:聂永刚